Learning of Physics with Scientific Approach in Boyolali Regency High School (Universitas Negeri Semarang, 2019)
This study aims to describe the implementation of the scientific approach carried out by teachers of State High Schools in Boyolali District. The study used a qualitative descriptive method. The research was carried out on three state high school in Boyolali Regency which were grouped according to the accreditation value. The research subjects were 3 physics teachers of class X and class X students of State High Schools in Boyolali Regency totaling 96 students. The instruments used are observation sheets, questionnaires, and interview guidelines. The results showed that the implementation of the scientific approach in Boyolali District High School was classified as medium. The highest core activity is observing and the lowest is trying. The factors that influence the implementation of the scientific approach by the teacher are infrastructure and laboratory facilities, and time constraints so that the teacher spends time on learning exercises.